2021
DOI: 10.1039/d1sc06052j
|View full text |Cite
|
Sign up to set email alerts
|

1-Zirconacyclobuta-2,3-dienes: synthesis of organometallic analogs of elusive 1,2-cyclobutadiene, unprecedented intramolecular C–H activation, and reactivity studies

Abstract: A detailed study of structure, bonding and reactivity of new 1-zirconacyclobuta-2,3-dienes is presented in comparison to a lighter Ti analog. We found a unique C–H activation at the widely used rac-(ebthi) ligand for that only occurs for Zr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 105 publications
3
23
0
Order By: Relevance
“…Whereas the Ti complex 1a showed no conversion at elevated temperatures, the Zr complexes 2a and 2b were transformed into the C–H activation products 3a / 3b that were described before. 21 In contrast, η 5 -indenyl complexes 2c and 2d could be converted within minutes at room temperature, producing a single new metallocene species that, according to its 1 H and 13 C{ 1 H} NMR spectra is not consistent with the four-membered aza-metallacyclobutene structure (Scheme 3). Instead, well-separated 13 C{ 1 H} resonances at 159.6/174.4 ( P 2c-SiMe3 ) and 157.9/176.0 ppm ( P 2d-SiMe3 ) as well as prominent IR bands at 1852 ( P 2c-SiMe3 ) and 1849 cm −1 ( P 2d-SiMe3 ) suggest the presence of an intact allene unit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the Ti complex 1a showed no conversion at elevated temperatures, the Zr complexes 2a and 2b were transformed into the C–H activation products 3a / 3b that were described before. 21 In contrast, η 5 -indenyl complexes 2c and 2d could be converted within minutes at room temperature, producing a single new metallocene species that, according to its 1 H and 13 C{ 1 H} NMR spectra is not consistent with the four-membered aza-metallacyclobutene structure (Scheme 3). Instead, well-separated 13 C{ 1 H} resonances at 159.6/174.4 ( P 2c-SiMe3 ) and 157.9/176.0 ppm ( P 2d-SiMe3 ) as well as prominent IR bands at 1852 ( P 2c-SiMe3 ) and 1849 cm −1 ( P 2d-SiMe3 ) suggest the presence of an intact allene unit.…”
Section: Resultsmentioning
confidence: 99%
“…1b). 21 In these complexes, selective C–H activation at the rac -(ebthi) and rac -(sbthi) (sbthi = dimethylsilylene-1,1′-bis(η 5 -tetrahydroindenyl)) ligands, respectively, produced a new type of tucked-in Zr( iv ) complexes that possesses a η 3 -propargyl/allenyl ligand ( 3a / 3b , Fig. 1b).…”
Section: Introductionmentioning
confidence: 99%
“…In consequence the chloride ligand in meso -4 is sterically protected in the meso -(ebthi) pocket which explains the necessity of higher temperatures and larger amounts of LiNMe 2 for formation of complex meso -3. Notably, attempts to prepare a dinuclear zirconocene amide complex from [( meso -(ebthi)ZrCl) 2 (μ-Me 3 SiC 3 SiMe 3 )] 56 also led to formation of the mononuclear complex meso -3 in low yield (Fig. S6 † ).…”
Section: Resultsmentioning
confidence: 99%
“…This strategy is advantageous because it allows access to first row transition metal catalysts for which alkylidynes such as A are exceedingly rare [33–34] . Fortunately, recent studies of Reiß and Beweries [48–49] demonstrated how complexes such as D can be accessed in one‐step using the trimethysilyl substituted 1,3‐dilithioallene “[Li 2 (Me 3 SiC 3 SiMe 3 )]” [50–51] reagent and dihalide precursor G . Their work inspired us to investigate how metallacyclobuta‐(2,3)‐dienes engage in the formation of cyclic ‐PPA and how such as scaffold can be a precursor to a rare alkylidene‐alkynyl motif.…”
Section: Methodsmentioning
confidence: 99%